2004
DOI: 10.1089/1076327041348374
|View full text |Cite
|
Sign up to set email alerts
|

Demineralized Bone Matrix-Induced Ectopic Bone Formation in Rats:In VivoStudy with Follow-up by Magnetic Resonance Imaging, Magnetic Resonance Angiography, and Dual-Energy X-Ray Absorptiometry

Abstract: The aim of this study was to further explore the use of magnetic resonance imaging (MRI), magnetic resonance angiography (MRA), and dual-energy X-ray absorptiometry (DEXA) to assess bone formation and blood circulation in a pedicled bone graft substitute. In 14 Wistar rats, initially 10 weeks old, heterogeneous demineralized femur bone matrix implants were wrapped in pedicled adductor thigh muscle flaps. One rat died after surgery. Subsequently, bone formation and maintenance of blood vessel functionality were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Since MRI contrast is sensitive to the molecular environment through changes in relaxation times T1 and T2, and apparent diffusion coefficient ADC, it can provide images and information that are not available using other techniques [19]. This technique has also been used in vitro and in vivo to study engineered tissues such as cartilage, heart valves, and ectopic bone [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Since MRI contrast is sensitive to the molecular environment through changes in relaxation times T1 and T2, and apparent diffusion coefficient ADC, it can provide images and information that are not available using other techniques [19]. This technique has also been used in vitro and in vivo to study engineered tissues such as cartilage, heart valves, and ectopic bone [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that ectopic bone induction was confirmed by implanting GDF-5 on the rat demineralized bone matrix carrier into the subcutaneous tissue (Chang et al, 1994) or muscle pouch of rats (Hotten et al, 1996). However, since the demineralized bone matrix itself has ectopic osteoinduction activity (Jergesen et al, 1991;Garraway et al, 1998;Hartman et al, 2004), it is not clear whether these results purely reflect the ectopic osteoinduction activity of GDF-5. Moreover, no studies have examined the correlation between the in vivo chondroosteoinduction ability of GDF-5 and the amount of induction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we have previously shown that temperature-responsive biomaterials based on poly­( N -isopropylacrylamide) (PiPAA) can be used in vitro as microcarriers of encapsulated cells to improve the retention and survival of delivered cardiomyocytes . In the field of regenerative medicine, noninvasive techniques are critical to identify and monitor cell implantation sites, degradation degree, and compatibility of implanted materials with the surrounding tissue. Therefore, the idea of an injectable hydrogel that can be continuously visualized in vivo in real time offers many advantages, such as the use of minimally invasive procedures and the possibility to dispense with cell labeling.…”
Section: Introductionmentioning
confidence: 99%